A déli határszakasz határőrizete a két világháború között - Suba, János (Közép-Európai Közlemények, 2015)
The Hungarian border control forces were reshaped by the Trianon Treaty to perform a twofold task. Their legal task was to guard the border, safeguard the relevant regulations and control distance and commuter traffic. Their covert task was to function as a military force along the border. It was their task to receive the first blows of a possible attack and thus slow down the enemy’s penetration into the country until the army’s main forces arrive. Therefore every third regiment of foot would be disguised as part of the border control forces up until 1938. In 1922, the new border guarding body was formed with the name of Customs Guard (Vámőrség) and it took over the roles of guarding the borders from the local police. From 1932 a restructuring starts to form it into a border control body. In 1938 it was made part of the Hungarian military forces and continued the guarding and defence of the borders as an armed body. Its highest organisational level was called brigade. Along the Southern border the hierarchic structure of the border guarding forces (patrols, platoons) was not changed, only their number was increased.